Colloidal synthesis of silicon nanoparticles in molten salts. Issue 24 (5th June 2017) - Shavel, A.; Guerrini, L.; Alvarez-Puebla, R. A.
Abstract : Unconventional colloidal synthesis of homogeneous silicon nanoparticles based on the reduction of silicon alkoxide precursors by magnesium in melted salt media under normal experimental conditions. Abstract : Silicon nanoparticles are unique materials with applications in a variety of fields, from electronics to catalysis and biomedical uses. Despite technological advancements in nanofabrication, the development of a simple and inexpensive route for the synthesis of homogeneous silicon nanoparticles remains highly challenging. Herein, we describe a new, simple and inexpensive colloidal synthetic method for the preparation, under normal pressure and mild temperature conditions, of relatively homogeneous spherical silicon nanoparticles of either ca. 4 or 6 nm diameter. The key features of this method are the selection of a eutectic salt mixture as a solvent, the identification of appropriate silicon alkoxide precursors, and the unconventional use of alkali earth metals as shape-controlling agents.